Risky decision-making in the Context of Contingency Management for Methamphetamine Use Disorder - Lake, Marilyn Toni (Department of Psychology, 2020)
Background: Risky decision-making is strongly implicated in adverse real-world risk-taking behaviour, and is associated with Substance Use Disorder, including Methamphetamine Use Disorder. Laboratory neurocognitive tasks typically utilized to assess risky decision-making have been able to distinguish participants with Substance Use Disorder from controls, although considerable heterogeneity is still evident within substance-using populations, which remains largely unexplained. Preliminary evidence has also tied risky decision-making to treatment outcomes, although no research has investigated risk-decision-making within Methamphetamine Use Disorder in the context of Contingency Management treatment. Methods: This study aimed to investigate decision-making on the Iowa Gambling Task and the Balloon Analogue Risk at baseline as both a function and predictor of treatment response on an 8-week treatment of Contingency Management. Of 26 participants with Methamphetamine Use Disorder, 17 responded to Contingency Management treatment, whilst 9 were non-responders. Using various mixed-effect modelling techniques and ANCOVA, performance by nonresponders were compared to responders, as well as a group of 19 healthy, nonsubstance-using control participants. Results: Group differences between non-responders, responders and controls were exclusively obtained on the Iowa Gambling Task. A trend-level (p=.051), large effect size (g=-0.98) was observed in the effect of reward magnitude between non-responders and healthy controls. More specifically, non-responders tended to seek-out large short-term rewards in spite of long-term losses relative to controls, however, groups did not also differ in effect of short-term loss magnitude. Non-responders also appeared to demonstrate poorer learning than healthy controls, although this finding was also at trend-level (p=.081) with a medium effect size (g =-0.63). In addition, results showed that responders and non-responders were differentially influenced by the frequency of outcomes, where responders demonstrated a greater preference for frequent rewards and infrequent losses relative to non-responders. This difference was at trend-level (p=.053) and the effect was moderately sized (g =-0.74). Impulsivity did not moderate group differences in decision-making, but did positively predict a greater likelihood of relapse at least once during Contingency Management (p =.035), although this effect was small (OR=1.10). Poor overall performance on the IGT appeared to predict a greater likelihood of prolonged relapse on Contingency Management following initial relapse, although this was at trend-level (p =.071) with a small effect size (OR=1.80). Conclusion: Findings provide evidence for individual differences in risky decision-making within Methamphetamine User Disorder, suggesting that risky decision-making is unlikely to be a homogeneous characteristic of substance-using populations, as is typically treated in the literature. Risky decision-making may also act as a risk factor for poor treatment success on Contingency Management, which in turn suggests that assessing risky decision-making of individuals with Methamphetamine Use disorder prior to commencing Contingency Management treatment might assist in identifying those at high risk.